Economic importance of the Belgian ports: Flemish maritime ports, Liège port complex and the port of Brussels – Report 2011 - Claude Mathys (National Bank of Belgium, 2013)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports (Antwerp, Ghent, Ostend, Zeebrugge), the Autonomous Port of Liège and the port of Brussels play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centers facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports, the Liège port complex and the port of Brussels for the period 2006 - 2011, with an emphasis on 2011. Focusing on the three major variables of value added, employment and investment, the report also provides some information based on the social balance sheet and an overview of the financial situation in these ports as a whole. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. As a result of the underlying calculation method the changes of indirect employment and indirect value added can differ from one another. (…) After the upturn in 2010, maritime cargo traffic in the Flemish ports continued to rise, albeit at a slower pace in 2011. Direct value added declined in the four ports in Flanders as a whole. Both maritime and non-maritime clusters as a whole were down. The only increase in value added occurred in the port of Zeebrugge. The value added of the non-maritime clusters in each port declined, while in the maritime cluster, the port of Antwerp was the only one to register a steep drop. Direct employment in the Flemish ports as a whole declined during the year 2011. This is true of both the maritime and non-maritime cluster. Only the port of Ghent registered a rise in employment in both clusters. Investment contracted in the Flemish ports as a whole for the third year in a row. The decline in investment was between 7 and 13 percent in the ports of Antwerp, Ghent and Ostend, whereas Zeebrugge recorded a negative rate of one-fifth in its investment levels in 2011. The volume of cargo handled in the port of Liège increased slightly in 2011. Direct value added rose in both clusters, while employment registered a decline in the maritime cluster and a rise in the nonmaritime cluster. After falling in 2010, investment picked up again in 2011 in both clusters. The volume of cargo handled at the port of Brussels rose in 2011. Value added in the maritime cluster was up but contracted in the non-maritime cluster. Employment increased in both clusters. The drop in investment recorded since 2009 continued throughout 2011. This report provides a comprehensive account of these issues, giving details for each economic sector, although the comments are confined to the main changes that occurred in 2011.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport; intermodality; public investments